Hydrogen Sulfide-Induced Vasodilation: The Involvement of Vascular Potassium Channels - Liu, Xiao-Yu; Qian, Ling-Ling; Wang, Ru-Xing (Frontiers in Pharmacology, 2022)
Hydrogen sulfide (H2S) has been highlighted as an important gasotransmitter in mammals. A growing number of studies have indicated that H2S plays a key role in the pathophysiology of vascular diseases and physiological vascular homeostasis. Alteration in H2S biogenesis has been reported in a variety of vascular diseases and H2S supplementation exerts effects of vasodilation. Accumulating evidence has shown vascular potassium channels activation is involved in H2S-induced vasodilation. This review aimed to summarize and discuss the role of H2S in the regulation of vascular tone, especially by interaction with different vascular potassium channels and the underlying mechanisms.